Integration of Perennial Values and Contemporary Demands: A Philosophical-Historical Review of Madrasah Curriculum Development - Nurul Mubin; M. Najib Alaziz; Desia Lu’luatussholihah (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
The rapid modernization of education often brings pragmatic tendencies that emphasize technical skills while potentially sidelining the moral and spiritual dimensions that are the core of Islamic education. Therefore, the development of the madrasah curriculum is an inevitability in responding to social dynamics, technological advancement, and 21st-century competency demands without neglecting its distinctive Islamic identity. This study aims to analyze the integration of perennial values with contemporary demands in madrasah curriculum development through a philosophical-historical review. The study employed a qualitative approach using a library research method based on a systematic literature review (SLR). The findings indicate that perennial values, such as ta’dib, morality, and divine orientation, remain relevant as the foundation of the curriculum to balance academic and spiritual growth. Historically, the madrasah curriculum in Indonesia has transformed from a traditional model toward integration with the national system. Practically, this integration is manifested through the implementation of digital literacy, 4C competencies, and the STEAM approach, where Islamic values serve as the spiritual foundation for science and technology. The main implementation challenges include limited facilities, teacher competence gaps, and resistance to change. Therefore, transformational leadership, enhanced teacher professionalism, and curriculum reconstruction that places adab as the core soul of every subject are needed so that madrasahs can produce graduates who are religious, adaptive, and competitive in the Society 5.0 era.